Physical Characteristics of Amorphous and Crystalline Coconut Sugar Powder with the Addition of Tricalcium Phosphate (TCP) as an Anticaking Agent - Bambang Nurhadi; Nandi Sukri; Rudy Adi Saputra; Fatonah Isnaini Wandhani; Afifah Indah Nurlita (International Journal of Food Science)
The coconut sugar powder produced by vacuum drying and conventional method has high hygroscopicity due to its high sugar content (mostly sucrose). Therefore, it is easier for caking to occur during storage. An anticaking agent such as tricalcium phosphate was therefore added to the powder to maintain its stability. The purpose of this research was to determine the physical characteristics of amorphous and crystalline coconut sugar after the addition of tricalcium phosphate (TCP) in different concentrations. The two types of coconut sugar were prepared by the conventional method, which gave it a predominantly crystalline structure, and the vacuum drying method, which gave it a mainly amorphous structure. The TCP at concentrations 0, 0.5%, and 1% was added to both types of the coconut sugar. The addition of the anticaking agent affected the water sorption of coconut sugar by decreasing the monolayer water content for both types of coconut sugar. TCP seemed to give more significant effect on decreasing the hygroscopicity of crystalline coconut sugar than the amorphous one, while similar trends were obtained in increasing flow ability of both types of coconut sugar. The capacity of TCP to cover the surface of the host coconut powder was proposed as the mechanism of TCP in decreasing hygroscopicity and increasing flow ability of the host powder.